Single dose testosterone administration increases men's facial femininity preference in a Chinese population. (May 2020) - Han, Chengyang; Zhang, Yinhua; Lei, Xue; Li, Xiangqian; Morrison, Edward R.; Wu, Yin
Highlights: Testosterone administration increases men's facial femininity preferences. Chinese men preferred femininity over masculinity in women's faces. Testosterone has a causal effect on men's facial preferences. Abstract: Sex hormones are thought to influence human mate preferences. Previous studies have reported mixed results regarding the association between men's testosterone levels and their mate preferences. The present study investigated the effect of testosterone administration on men's facial femininity preference. Heterosexual Chinese male participants (n = 140) received a single dose of 150 mg testosterone or placebo gel in a double-blind, placebo-controlled, between-participant design. Results showed that Chinese men demonstrated general preferences for feminized women's faces, consistent with previous results from the Western population. More importantly, men showed stronger attraction to femininity in women's faces three hours after testosterone administration than at the beginning of the session. In the placebo group, no significant change in facial femininity preferences was found between time points. These results indicate that exogenous testosterone increases men's facial femininity preferences in a Chinese population.